Altered Cholesterol Homeostasis in Huntington’s Disease - Kacher, Radhia; Mounier, Coline; Caboche, Jocelyne; Betuing, Sandrine (Frontiers in Aging Neuroscience, 2022)
Huntington's disease (HD) is an autosomal dominant genetic disorder caused by an expansion of the CAG repeat in the first exon of Huntingtin's gene. The associated neurodegeneration mainly affects the striatum and the cortex at early stages and progressively spreads to other brain structures. Targeting HD at its earlier stages is under intense investigation. Numerous drugs were tested, with a rate of success of only 3.5% approved molecules used as symptomatic treatment. The restoration of cholesterol metabolism, which is central to the brain homeostasis and strongly altered in HD, could be an interesting disease-modifying strategy. Cholesterol is an essential membrane component in the central nervous system (CNS); alterations of its homeostasis have deleterious consequences on neuronal functions. The levels of several sterols, upstream of cholesterol, are markedly decreased within the striatum of HD mouse model. Transcription of cholesterol biosynthetic genes is reduced in HD cell and mouse models as well as post-mortem striatal and cortical tissues from HD patients. Since the dynamic of brain cholesterol metabolism is complex, it is essential to establish the best method to target it in HD. Cholesterol, which does not cross the blood-brain-barrier, is locally synthesized and renewed within the brain. All cell types in the CNS synthesize cholesterol during development but as they progress through adulthood, neurons down-regulate their cholesterol synthesis and turn to astrocytes for their full supply. Cellular levels of cholesterol reflect the dynamic balance between synthesis, uptake and export, all integrated into the context of the cross talk between neurons and glial cells. In this review, we describe the latest advances regarding the role of cholesterol deregulation in neuronal functions and how this could be a determinant factor in neuronal degeneration and HD progression. The pathways and major mechanisms by which cholesterol and sterols are regulated in the CNS will be described. From this overview, we discuss the main clinical strategies for manipulating cholesterol metabolism in the CNS, and how to reinstate a proper balance in HD.